Modified Copy, Cover, and Compare Using Multiplication Fact Triangles: The Effects on Math Fact Accuracy and Fluency - Fossum, Jenette Ward (My University, 2013)
This study examined the use of a Modified Copy, Cover, and Compare math intervention to observe the effect it would have on students' math fact accuracy and fluency. The six week study was carried out in a rural midwestern middle and high school with students involved in the RtI Math intervention program and special education math pull out program in the high school. The study displayed a positive relationship between participation in the study and some increase in the students overall math achievement as measured by the STAR Math test and a decrease in their digits incorrect per minute as measured by a Mastering Math Facts Two Minute Timing. The study displayed room for growth in regard to future research with different participants, environments, controls and frequency in delivering the intervention.
Keywords: Mastering Math Facts Two Minute Timing; math fact; middle school; high school; accuracy; fluency; RtI Math; students; midwest; rural; STAR Math test; Special Education; Educational Leadership; math; Compare math; Modified Copy, Cover, and Compare